2020
DOI: 10.1016/j.oraloncology.2019.104521
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported financial toxicity and adverse medical consequences in head and neck cancer

Abstract: Objectives-Financial toxicity (FT) is a significant barrier to high-quality cancer care, and patients with head and neck cancer (HNCA) are particularly vulnerable given their need for intensive support, daily radiotherapy (RT), and management of long-term physical, functional, and psychosocial morbidities following treatment. We aim to identify predictors of FT and adverse consequences in HNCA following RT.Materials and Methods-We performed a prospective survey study of patients with HNCA seen in follow-up at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 43 publications
3
94
2
Order By: Relevance
“…We have previously shown that 33% of head and neck cancer patients going through radiation treatment reported at least a moderate financial burden from treatment, and this was associated with increased treatment non-compliance. 46 While 79% of participants in this study reported that financial issues were not a concern, possibly reflecting the relatively affluent population studied here, options that incorporate fewer in-person surveillance visits and more remote monitoring may help offset these patientborne burdens without compromising ability to detect recurrences.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have previously shown that 33% of head and neck cancer patients going through radiation treatment reported at least a moderate financial burden from treatment, and this was associated with increased treatment non-compliance. 46 While 79% of participants in this study reported that financial issues were not a concern, possibly reflecting the relatively affluent population studied here, options that incorporate fewer in-person surveillance visits and more remote monitoring may help offset these patientborne burdens without compromising ability to detect recurrences.…”
Section: Discussionmentioning
confidence: 88%
“…treatment noncompliance [46]. Although 79% of participants in this study reported that financial issues were not a concern, possibly reflecting the relatively affluent population studied here, options that incorporate fewer in-person surveillance visits and more remote monitoring may help offset these patient-borne burdens without compromising ability to detect recurrences.…”
Section: Interest In Altered Surveillancementioning
confidence: 85%
“…FT is associated with the decline of QOL as well as increased mortality, possibly through a hesitancy to pursue additional treatment or non-compliance [ 9 , 10 , 11 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer (HNC) patients are at particularly high risk for FT as they often require multi-modal therapy, have more out-of-pocket costs, have an increased reliance on cost-coping strategies, and are more likely to suffer production losses as a result of their disease and treatment [ 5 , 6 , 7 , 8 ]. Consequently, increased financial difficulties in HNC has been linked to impaired quality of life (QOL), increased missed appointments, reduced compliance with medications, and worse medical outcomes including survival [ 9 , 10 , 11 ]. Therefore, urgent mitigation strategies for FT among HNC patients are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Though cancer-related financial toxicity impacts patients across the spectrum of diseases, evidence suggests that there are particular aspects of financial toxicity that affect head and neck cancer patients, who make up an estimated 65 000 new cases annually in the United States and 550 000 annual cases worldwide. Only a small number of studies have focused solely on the financial hardship in head and cancer patients, but the limited evidence suggests that approximately one third of head and neck cancer patients report between moderate and catastrophic levels of financial hardship [ 14 , 15 ]. A deeper understanding of the sources of financial hardship in head and neck cancer patients is needed to design interventions and develop strategies to mitigate this problem.…”
Section: Introductionmentioning
confidence: 99%